Effect of Classic Foot Massage on Vital Signs, Pain, and Nausea/Vomiting Symptoms After Laparoscopic Cholecystectomy - Cankaya, Askeri; Saritas, Serdar (Lippincott Williams & Wilkins, 2018)
This semiexperimental study on the effects of foot massage recruited 88 patients who underwent laparoscopic cholecystectomy at the general surgery clinics of our hospital in Turkey (June 2017 to May 2018). Patients were assigned to either the intervention group (n=44, 10 min of classic foot massage) or the control group (n=44, no intervention). Pretest assessment, intervention, and posttest assessment were conducted within 1 to 6 hours postoperatively. Outcome measures included vital signs, pain, and nausea/vomiting symptoms. The intervention was associated with a significant decrease in pain scores and incidence of nausea. Despite being associated with an increase in body temperature, the intervention was also associated with a decrease in systolic blood pressure without increasing diastolic blood pressure or respiratory rate, suggesting a positive effect on blood circulation. Classic foot massage may serve as an affordable and useful way to help improve pain, nausea, and blood circulation after laparoscopic cholecystectomy.
Keywords: classic foot massage; health care providers; laparoscopic cholecystectomy; nausea; postoperative pain; vital signs; vomiting